A new criterion for glass-forming ability based on both devitrification and solidification processes. (September 2021) - Li, Zijing; Wang, Ji; Pan, Shaopeng; Affouard, Frédéric; Zhang, Suhong; Feng, Shidong; Liu, Yingdan; Wang, Li-min
Abstract: Based on the time-temperature-transformation interpretation, a new criterion for glass forming ability, Z = [( T x - T g )/( T l - T g )][( T l – T l(c) )/( T l - T g )] 0.556, is proposed, where T g, T x, T l and T l(c) respectively denote the glass transition temperature, the onset crystallization temperature upon heating, the liquidus temperature and the onset solidification temperature of the liquid upon cooling. The Z parameter jointly considers the stability of the liquid and the devitrification of glassy phases. A non-linear relationship between the parameter Z and the critical glassy size d c has been found to be log ( d c ) cal = 0.1392 + 17.0616Z - 41.985(Z) 2, showing stronger correlation than other earlier reported parameters. The advantage of using Z as a GFA parameter is that it roughly reflects the relative influences of the thermodynamics and kinetics of the systems on glass formation. In addition, the parameter describes the stability of liquid in the course of being quenched from above liquidus temperature. Highlights: The present parameter shows a stronger correlation with GFA than other combined parameters of characteristic temperatures. The present parameter throws special light on the stability of liquid in the course of quenching from above liquidus temperature. The present parameter is capable of roughly reflecting the relative influences of the thermodynamics and kinetics on glass formation of the systems.